2009
DOI: 10.1128/aem.01262-09
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Lineages of the Genus Escherichia

Abstract: Extended multilocus sequence typing (MLST) analysis of atypical Escherichia isolates was used to identify five novel phylogenetic clades (CI to CV) among isolates from environmental, human, and animal sources. Analysis of individual housekeeping loci showed that E. coli and its sister clade, CI, remain largely indistinguishable and represent nascent evolutionary lineages. Conversely, clades of similar age (CIII and CIV) were found to be phylogenetically distinct. When all Escherichia lineages (named and unname… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
244
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(275 citation statements)
references
References 64 publications
16
244
1
6
Order By: Relevance
“…The small distances and consistent grouping of the two environmentals in all culture conditions, together with differences in their ecological strategy compared with other strains, suggest that they do indeed form a separate ecotype as proposed earlier, where extra-intestinal open environments serve as their primary habitat (Walk et al, 2009;Luo et al, 2011). It should be noted that E. coli strains belonging to the same clades as the strains used in this study are commonly detected in bird feces as well (Clermont et al, 2011), but it is currently not clear if these strains cycle between birds and the environment or whether different ecotypes with distinct primary habitats do exist within those lineages.…”
Section: Signatures Of Ecological Adaptationmentioning
confidence: 86%
See 1 more Smart Citation
“…The small distances and consistent grouping of the two environmentals in all culture conditions, together with differences in their ecological strategy compared with other strains, suggest that they do indeed form a separate ecotype as proposed earlier, where extra-intestinal open environments serve as their primary habitat (Walk et al, 2009;Luo et al, 2011). It should be noted that E. coli strains belonging to the same clades as the strains used in this study are commonly detected in bird feces as well (Clermont et al, 2011), but it is currently not clear if these strains cycle between birds and the environment or whether different ecotypes with distinct primary habitats do exist within those lineages.…”
Section: Signatures Of Ecological Adaptationmentioning
confidence: 86%
“…It spans a genetic continuum from the human associated enteric E. coli to several atypical clades that are frequently detected in the environment and in birds (Clermont et al, 2011). All clades share the same core genes (that is, atypical strains exhibit all genes considered typical for enteric E. coli) and show remarkable biochemical similarities, which left them categorized as the same species (Walk et al, 2009). Subsequently, a taxonomic placement of these atypical clades as different species was proposed because (i) phylogenetic analysis cluster human enteric strains together and apart from atypical strains, (ii) several genes that are considered important for adaptation to distinct primary habitats (the human gut versus the environment) are specifically enriched in the individual groups and (iii) the exchange of genetic material has been shown to occur predominantly within strains sharing the same primary habitat (Luo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The orders-of-magnitude higher abundances of these clades in environmental samples relative to those in human feces and the clinic (9) indicate that they represent truly environmentally adapted organisms (meaning that they are not associated primarily with mammal hosts). Consistent with this interpretation, a recent study found that strains of clades C-III, -IV, and -V form biofilms more readily, outcompete typical E. coli strains at low temperatures (which characterize the environment compared with the gastrointestinal tract of warm-blooded hosts), and are nonpathogenic in a mouse model of septicemia (13).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this interpretation, a recent study found that strains of clades C-III, -IV, and -V form biofilms more readily, outcompete typical E. coli strains at low temperatures (which characterize the environment compared with the gastrointestinal tract of warm-blooded hosts), and are nonpathogenic in a mouse model of septicemia (13). Furthermore, screening of 2,701 strains from humans, animals, and the environment identified an additional 57 environmental clade strains, and these strains were found more often in environmental and bird samples than in human samples (9). These studies consistently support the hypothesis that the environmental clades substantially expand the known ecological niche of E. coli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation